Spectrum of EGFR gene mutations and ALK rearrangements in lung cancer patients in Turkey - Sag, Sebnem Ozemri (Springerplus, 2016)
The EGFR gene and ALK rearrangements are two genetic drivers of non-small cell lung cancer (NSCLC). The frequency of EGFR mutations and ALK rearrangement varies according to not only ethnicity but also gender, smoking status and the histological type of NSCLC. In the present study, we demonstrated the distribution of EGFR mutations in 132 NSCLC patients by using a pyrosequencing technique and the distribution of ALK rearrangements in 51 NSCLC patients by using fluorescent in situ hybridization technique in Turkey. Additionally, we compared the clinicopathological data of NSCLC patients with the mutation status of EGFR in their cancerous tissues. Both EGFR mutations and ALK rearrangements were identified in 19 (14.39 %) and 1 (1.96 %) patients, respectively. We found EGFR mutations in codon 861, 719 and 858 with the ratios of 10.52 % (2/19), 10.52 % (2/19) and 31.58 % (6/19), respectively, and deletion of exon 19 in 47.37 % (9/19) of the patients. We found the frequency of EGFR mutations to be significantly higher in female patients and nonsmokers (p = 0.043, p = 0.027, respectively). Consequently, we found EGFR mutations to be more frequent in female patients and nonsmokers. Future studies on larger patient groups would provide more accurate data to exhibit the relationship between EGFR mutations and ALK rearrangements and the clinicopathological status.